Empowerment of Street Vendors by the Nur Ala Nur Grand Mosque in Panyabungan Through the Maqāṣid al-Sharī‘ah Index (MSI) Measurement - Suhardina; Mustapa Khamal Rokan; Muhammad Syahbudi (Al-Muamalat, 2025)
This study examines the role of Masjid Agung Nur Ala Nur Panyabungan in empowering surrounding street vendors, using the Maqāṣid al-Sharī‘ah Index (MSI) as an analytical framework. The objectives of the research are to assess the conditions, opportunities, and challenges faced by street vendors in this mosque-based economic model, and to explore how Maqāṣid al-Sharī‘ah principles can inform sustainable empowerment strategies. The study employs a qualitative descriptive design, involving in-depth interviews, participatory observation, and document analysis, with participants including mosque administrators, street vendors, and congregants. The results highlight that while the mosque contributes to local economic activity, the empowerment initiatives remain fragmented, with gaps in structured training, financial management expertise, and collaboration with local stakeholders. The MSI findings show that the dimension of "Upholding Justice" scored highest, reflecting the mosque's role in ensuring fair business practices. However, the "Educating Individuals" dimension was weakest, indicating a need for capacity-building programs. The study concludes that for mosques to realize their full potential as centers of economic empowerment, there must be a more strategic approach, including enhanced training, financial transparency, and partnerships with Islamic microfinance institutions.